Revisiting the oldest manure of India, Kunapajala: Assessment of its animal waste recycling potential as a source of plant biostimulant - Mukherjee, Shibasis; Basak, Ayanita; Chakraborty, Argha; Goswami, Rupak; Ray, Krishnendu; Ali, Md. Nasim; Santra, Sayantan; Hazra, Alok Kumar; Tripathi, Sudipta; Banerjee, Hirak; Layek, Jayanta; Panwar, Azad S.; et al. (Frontiers in Sustainable Food Systems, 2023)
India’s oldest organic manure, most commonly referred to as Kunapajala, has a long history of over 1000 years in crop cultivation. Kunapajala is primarily a dairy excreta-based, in-situ decomposition technology of animal waste and can potentially provide an eco-friendly pipeline for recycling bio-waste into essential plant nutrients. Here, we aimed to assess the waste recycling and plant biostimulant potential of Kunapajala prepared from livestock or fish wastes over different decomposition periods, e.g., (0, 30, 60, and 90-days). An in-situ quantification of the livestock- (lKPJ) and fish-based Kunapajala (fKPJ) reveals a dynamic landscape of essential plant primary nutrients, e.g., (0.70>NH4-N<3.40 g•L-1), (100.00>P2O5<620.00 mg•L-1), and (175.00>K2O<340.00 mg•L-1), including other physico-chemical attributes of Kunapajala. Using correlation statistics, we find that the nutrient niche of Kunapajala depicts a significant transformation with microbial dynamics, abundance, and diversities, delineating microbial interface to animal waste decomposition and plant growth promotion. Importantly, this study also reports the indole 3-acetic acid (IAA) content (40.00>IAA<135.00 µg•ml-1) in Kunapajala. Functional analyses of derived bacterial isolates further elucidate the mechanism of plant biostimulant potential of Kunapajala, including the 16S ribotyping of two best-performing plant beneficial bacteria. In-planta assays finally demonstrate the bio-stimulative effects of Kunapajala and these two bacterial isolates on seed germination, root-shoot length, and other important agronomic, physio-biochemical traits in rice. Together, our findings establish that Kunapajala can be recommended as a source of plant biostimulant to improve crop quality traits in rice. Overall, this work highlights Kunapajala, for the first time, as a promising low-cost microbial technology that can have a dual function of animal waste recycling and plant nutrient recovery to promote sustainable intensification in agroecosystems.